LEVERAGING PHONETICS TO ELEVATE PRONUNCIATION IN SECOND LANGUAGE ACQUISITION IN STIT AL-ITTIHADIYAH NORTH LABUHANBATU - Pasaribu, Gumarpi Rahis; Zang, Yunhao (Universitas Muria Kudus, 2024)
In an increasingly globalized world, mastering pronunciation in a foreign language is essential for effective communication. This study investigates the impact of integrating phonetics training into second language acquisition (SLA) at STIT AL-Ittihadiyah Labuhanbatu Utara, focusing on enhancing pronunciation skills among students. Utilizing a mixed-methods approach, the research combined quantitative surveys, qualitative interviews, and classroom observations with pre- and post-intervention assessments to evaluate the effectiveness of phonetics training. A 12-week program incorporating both traditional methods and technological tools, such as speech recognition software and pronunciation apps, was implemented. Findings reveal that phonetics training significantly improved students' pronunciation accuracy by addressing native language interference and enhancing phonemic awareness. The use of technology was particularly beneficial, accelerating progress and providing interactive feedback. The study underscores the importance of integrating phonetics, phonemic awareness, and technology to achieve effective pronunciation and communication skills in a second language. It highlights the need for continued research into combined approaches to optimize SLA outcomes and supports the development of comprehensive language education strategies at STIT AL-Ittihadiyah Labuhanbatu Utara and similar institutions.